Attitude of Dairy Farmers Towards Cultivation of Green Fodder Crops in Bidar District of Karnataka - Rathod , Prakashkumar (Indian Journal of Veterinary Sciences and Biotechnology, 2017)
An ex-post-facto exploratory study was conducted to assess the attitude of dairy farmers towards cultivation of green fodder crops and constraints faced by them for fodder cultivation in Bidar district of Karnataka, India using an attitude scale through personal interview method. The study reported that majority of the respondents had medium level of favorable attitude towards green fodder cultivation and the variables education and scientific orientation of the farmers was found to be significantly correlated with attitude towards green fodder cultivation. The respondents perceived that non-availability of inputs and scarcity of water was the major constraints for cultivation of fodder in the study area. The study concluded that, there is a need to educate the farmers about green fodder cultivation and feeding through various extension approaches for improved dairy production in the study area.